2021
DOI: 10.1021/acs.chemmater.0c04440
|View full text |Cite
|
Sign up to set email alerts
|

[Methylhydrazinium]2PbBr4, a Ferroelectric Hybrid Organic–Inorganic Perovskite with Multiple Nonlinear Optical Outputs

Abstract: An expansive library of structurally complex two-dimensional (2D) and three-dimensional (3D) lead halide perovskites has emerged over the past decade, finding applications in various aspects of photon management: photovoltaics, photodetection, light emission, and nonlinear optics. Needless to say, the highest degree of structural plasticity enjoys the former group, offering a rich playground for modifications of relevant optoelectronic parameters such as exciton energy. Structural tailorability is reflected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(206 citation statements)
references
References 66 publications
6
183
3
Order By: Relevance
“…Hybrid lead halide perovskites crystallizing in various crystal structures, including zero-, one-, two-and three-dimensional (0D, 1D, 2D and 3D), have attracted a lot of interest in recent years due to their various functional properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Regarding 3D perovskites, the most famous ones are MAPbI 3 and FAPbI 3 (MA = methylammonium; FA = formamidinium) since they exhibit excellent photovoltaic properties with a power conversion efficiency exceeding 21% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid lead halide perovskites crystallizing in various crystal structures, including zero-, one-, two-and three-dimensional (0D, 1D, 2D and 3D), have attracted a lot of interest in recent years due to their various functional properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Regarding 3D perovskites, the most famous ones are MAPbI 3 and FAPbI 3 (MA = methylammonium; FA = formamidinium) since they exhibit excellent photovoltaic properties with a power conversion efficiency exceeding 21% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Mączka and coworkers recently presented linear and nonlinear optical studies of exciton emission of 2D layered perovskite MHy 2 PbBr 4 with ferroelectric property (Table 2, entry 16). [89] In their work, they also observed that the sharp CE emission is clearly visible under 2PA excitation conditions at 800 nm and 1000 nm but not under 1PA excitation (367 nm). Temperature-resolved studies (80-370 K) showed that CE emission is present up to room temperature, although it significantly subsides in intensity and shifts towards longer wavelengths, fully merging with self-trapped excitons (STEx) emission at ≈320 K. They have also studied exciton luminescence of the same material using longwavelength 1300 nm femtosecond laser; at that wavelength the luminescence is of mixed three-photon and four-photon origin, as revealed by power-dependent measurements.…”
Section: Using 2pa For Studying Electronic Structure Of Perovskitesmentioning
confidence: 87%
“…[177] Surprisingly, beside the 3D lead bromide perovskite structure, the MHy cations can simultaneously template the n = 1 structure (MHy) 2 PbBr 4 . [178] Just recently, FA 2 PbBr 4 (n = 1) phases with the corrugated (110)-orientated structure were reported in two polymorphs: triclinic (t-FA 2 PbBr 4 ) and monoclinic (m-FA 2 PbBr 4 ) (Table 2). [139] The FA 2 PbBr 4 phases are synthesized in pure form with the use of excess FABr salt and subsist in a labile equilibrium with the 3D FAPbBr 3 phase.…”
Section: Lead Bromide Perovskites With Thick Layer Thickness (N > 1)mentioning
confidence: 99%
“…As discussed above, structurally and synthetically, the majority of bulk, lead bromide perovskites reported are the thin-layered (n = 1) members. [55,[88][89][91][92][93][95][96][97][102][103][104][105]113,[123][124][125][126][128][129][141][142][143][144][145][146][147] In the early 1990s, Thorn and colleagues report the first evidence of thick-layer lead halide perovskites (n > 1) by producing films of (C 9 H 19 NH 3 ) 2 (CH 3 NH 3 )Pb 2 I 7 and (C 9 H 19 NH 3 ) 2 (CH 3 NH 3 ) nÀ 1 Pb n Br 3n + 1 (n = 1-3) series with the nonylammonium spacer cation, along with films of (PhNH 3 ) 2 (CH 3 NH 3 )Pb 2 I 7 with Ph: phenylammonium. [148] Although unable to obtain single crystal structures at the time, Thorn and colleagues noted the excitonic absorption peak of (C 9 H 19 NH 3 ) 2 (CH 3 NH 3 )Pb 2 Br 7 films at 430 nm and (C 9 H 19 NH 3 ) 2 (CH 3 NH 3 ) 2 Pb 3 Br 10 at 450 nm, lower in energy than their n = 1 member.…”
Section: Lead Bromide Perovskites With Thick Layer Thickness (N > 1)mentioning
confidence: 99%